Decoding organizational culture: A study of Malaysian construction firms - Wang, C.; Abdul-Rahman, H. (Academic Journals, 2010)
The paper studies the cultural practices influencing business performance in over 327 Malaysian contractors. A national-wide questionnaire survey has been conducted to determine the current enterprise culture, leadership styles and enterprise axiology in Malaysian construction contracting organizations. Findings reveal that the ``monkey culture'', which is epitomizing teamwork and loyalty, is considered as the most applicable type for the organizational culture in Malaysia. People oriented management style has as many supporters as that of the task oriented management style in Malaysian contractors. However, more than 50% contractors have difficulties in determining their organizational culture. Making profit and seeking customers' satisfaction are the major concerns in a Malaysian contracting organization, which is synchronous with the western enterprise axiology.